KEPRIBADIAN PEGAWAI NEGERI SIPIL YANG BERINTEGRITAS BERDASARKAN TEORI EYSENCK - Ariesta Handoko Pratama; Supriyadi Supriyadi (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
Corruption in government institution has been known by the public and Indonesia becomes one of the most corrupt countries in the world (Ditkumham Bappenas, 2012). Corruption among public service is caused by leaders or civil servants, who fail to suppress their personal desires, fail to work accordance with moral values, and fail to meet up the expected value needed by the public during their services in work field (Rahardian & Budi, 2012). It happened because integrity of the civil servants was poor. Corruption is a reflection of the personality and integrity refers to the quality of a person's personality traits (Nucci and Narvaes in Putra, 2010). Accordingly, personality is being expected as the aspect that determines integrity of individual. This research is quantitative study through two analysis methods; they are One Way ANOVA and Rank Spearman correlation. The sampling method used is multistage random sampling. Respondents involved 380 government civil servants in Bali. Data was collecting through Eysenck Personality Inventory (EPI-A) (?=0.776) that consist of 60 items and civil servants integrity scale (?=0.779) that consist of 21 items. The result was found the probability coefficient is 0.006 (p<0.01), it show there differences of civil servants integrity between type of personality of Eysenck's Theory. Side that, the result show there correlations between traits of personality, that is activity (p<0.01), sociability (p<0.05), reflectiveness (p<0.01), responsibility (p<0.01), and self esteem (p<0.01) with civil servants integrity. It can be concluded that the traits of personality influence in determine quality of civil servants integrity. Keywords: Eysenck’s Theory of Personality, Integrity, Civil Servant